Eriocheir sinensis vesicle-associated membrane protein can enhance host cell phagocytosis to resist Spiroplasma eriocheiris infection. Issue 128 (September 2022) - Wang, Yaqin; Miao, Yanyang; Shen, Qingchun; Liu, Xueshi; Chen, Minyi; Du, Jie; Ning, Mingxiao; Bi, Jingxiu; Gu, Wei; Wang, Li; Meng, Qingguo
Abstract: Vesicle-associated membrane protein (VAMP) belongs to the receptor protein on the membrane of the secretory transport vesicle and involves in host immune function. The intracellular pathogen Spiroplasma eriocheiris could cause Eriocheir sinensis tremor disease. In a previous study, it was found E. sinensis VAMP (EsVAMP) was differently expressed in S. eriocheiris infection by proteomics analysis. This study mainly aims at the function of EsVAMP in the process of the S. eriocheiris infection. The length of EsVAMP gene was 1681 bp, which contained a 395 bp open reading frame, 90 bp 5′-non-coding region (UTR) and 1277 bp 3′-UTR. The results of qPCR showed that EsVAMP was expressed highly in hemocytes and nerves, followed by gills, intestines and hepatopancreas, and lowly expressed in heart and muscles. EsVAMP in hemocytes was up-regulated after S. eriocheiris infection. After EsVAMP over-expression and S. eriocheiris infection, the RAW264.7 cell morphology and cell viability of the experiment group were significantly better than the control group. Meanwhile, the copy number of S. eriocheiris in the experiment group was significantly lower than that in the control group. After EsVAMP and pCMV-Cre-mCherry were ligated and transfected into RAW264.7 cells, it was found that EsVAMP and lysosome co-localized. Meanwhile, the phagocytosed inactivated S. eriocheiris number and phagocytosed efficiency in RAW264.7 cells were increased significantly. The interference experiment was carried out by synthesizing EsVAMP dsRNA to verify that the EsVAMP transcriptions were successfully suppressed. The S. eriocheiris copy number and the mortality of crab increased significantly after EsVAMP RNAi and S. eriocheiris infection. Meanwhile, the phagocytosed inactivated S. eriocheiris number and phagocytosed efficiency in hemocytes decreased significantly after EsVAMP RNAi and S. eriocheiris infection. These results showed that VAMP was involved in the cell phagocytosis to resist pathogen infection. Highlights: A vesicle-associated membrane protein, EsVAMP, was obtained from Eriocheir sinensis and related with Spiroplasma eriocheiris infection. The cell morphology, cell viability was induced to resist S. eriocheiris infection after EsVAMP over-expression in RAW264.7 cells. EsVAMP and lysosome was co-localized to increase the phagocytosis of RAW264.7 cells after EsVAMP over-expression in RAW264.7 cells. The S. eriocheiris copy number and the mortality of crab was increased significantly and the hemocytes phagocytosis to inactivated S.eriocheiris decreased significantly after EsVAMP RNAi.